2006
DOI: 10.1111/j.1551-2916.2006.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Crystalline‐Oriented (K0.5Na0.5)NbO3 Piezoelectric Ceramics with a Sintering Aid of CuO

Abstract: The microstructural development of crystalline-oriented (K 0.5 Na 0.5 )NbO 3 (KNN)-based piezoelectric ceramics during sintering was investigated. The addition of CuO as a sintering aid was found to be effective for fabricating highly oriented and dense KNN ceramics. KNN specimens containing 0.5-1.0 mol% CuO sintered at 11001C for 1 h were found to have relative densities and pseudo-cubic {100} orientation degrees of 95% or higher. In the early stages of sintering, KNN is formed in the reaction between complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(136 citation statements)
references
References 18 publications
3
128
1
Order By: Relevance
“…Therefore, there is a great need to develop lead-free piezoelectric ceramics with excellent piezoelectric properties for replacing the lead-containing ceramics in various applications. Several lead-free piezoelectric ceramics such as Bi 0.5 Na 0.5 TiO 3 -based materials, [1][2][3][4] Bi-layered structure materials, 5,6 tungsten bronze-type materials, 7 BaTiO 3 -based ceramics, 8 and alkaline niobatebased materials [9][10][11][12][13][14][15][16][17][18][19][20][21] have been extensively investigated. An important progress of grain-oriented alkaline niobate-based ceramics has been reported recently 22 and piezoelectric ceramics should be "lead-free at last."…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a great need to develop lead-free piezoelectric ceramics with excellent piezoelectric properties for replacing the lead-containing ceramics in various applications. Several lead-free piezoelectric ceramics such as Bi 0.5 Na 0.5 TiO 3 -based materials, [1][2][3][4] Bi-layered structure materials, 5,6 tungsten bronze-type materials, 7 BaTiO 3 -based ceramics, 8 and alkaline niobatebased materials [9][10][11][12][13][14][15][16][17][18][19][20][21] have been extensively investigated. An important progress of grain-oriented alkaline niobate-based ceramics has been reported recently 22 and piezoelectric ceramics should be "lead-free at last."…”
Section: Introductionmentioning
confidence: 99%
“…71) Takao et al examined the microstructure development in a rather simple system, K 0.5 Na 0.5 NbO 3 with a sintering aid CuO. 16) Kikuchihara and Kimura examined the microstructure development in K 0.5 Na 0.5 NbO 3 with and without CuO. 35) Here, the microstructure development in K 0.5 Na 0.5 NbO 3 without CuO is shown in Fig.…”
Section: K 05 Na 05 Nbomentioning
confidence: 99%
“…Takao et al reported that the elimination of pores to less than 10 vol % is necessary for the growth of the template grains. 16) This means that the pores hinder the grain boundary migration. When the pore volume decreases to less than 10 vol %, the pinning and drag effects of pores diminish.…”
Section: Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations